An Eye in the Replication Stress Response: Lessons From Tissue-Specific Studies in vivo - Matos-Rodrigues, Gabriel E.; Martins, Rodrigo A. P. (Frontiers in Cell and Developmental Biology, 2021)
Several inherited human syndromes that severely affect organogenesis and other developmental processes are caused by mutations in replication stress response (RSR) genes. Although the molecular machinery of RSR is conserved, disease-causing mutations in RSR-genes may have distinct tissue-specific outcomes, indicating that progenitor cells may differ in their responses to RSR inactivation. Therefore, understanding how different cell types respond to replication stress is crucial to uncover the mechanisms of RSR-related human syndromes. Here, we review the ocular manifestations in RSR-related human syndromes and summarize recent findings investigating the mechanisms of RSR during eye development in vivo. We highlight a remarkable heterogeneity of progenitor cells responses to RSR inactivation and discuss its implications for RSR-related human syndromes.